La fuga del capitano Charles Lux dalla fortezza di Glatz (Kłodzko) in Bassa Slesia: la narrazione tra funzione estetica e persuasiva - Palmarini, Luca (Romanica Silesiana, 2020)
This article analyzes the presence of propaganda and its persuasive strategies in the narration born on the occasion of the famous escape in 1912 by Charles Lux, captain of the French army, from the several Prussian fortress of Glatz, present-day Kłodzko (Poland). In particular, through the analysis of the articles published by the French press after his escape, as well as the captain memoirs, it can be seen how the persuasive technique acquires a particular meaning in the narration.